2017
DOI: 10.1016/j.actbio.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Engineered myocardium model to study the roles of HIF-1α and HIF1A-AS1 in paracrine-only signaling under pathological level oxidative stress

Abstract: Studying heart tissue is critical for understanding and developing treatments for cardiovascular diseases. In this work, we fabricated precisely controlled and biomimetic engineered model tissues to study how cell-cell and cell-matrix interactions influence myocardial cell survival upon exposure to pathological level oxidative stress. Specifically, the interactions of endothelial cells (ECs) and cardiomyocytes (CMs), and the role of hypoxia inducible factor-1α (HIF-1α), with its novel alternative regulator, HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Previous characterizations from our group have shown that cells differentiated using this protocol are very similar to HUVECs in mRNA and protein expression as well as in tube formation ability. 43 In this study, we characterize the cells further under flow. iECs seeded into both the single channel device and the MOC appeared morphologically similar to primary endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous characterizations from our group have shown that cells differentiated using this protocol are very similar to HUVECs in mRNA and protein expression as well as in tube formation ability. 43 In this study, we characterize the cells further under flow. iECs seeded into both the single channel device and the MOC appeared morphologically similar to primary endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…39 In previous studies, we have characterized the phenotypical and functional properties of these iEC under static culture conditions. 43 In this study, we seeded iECs into a microfluidic device with a single channel (0.1 mm high  1 mm wide  10 mm long, Figure 4) to apply physiological-level shear stress and examined the morphology and expression of endothelial cell-specific markers under flow. iECs were seeded into the single-channel microfluidic device (Figure 4(b)) and 24 h after seeding, the device was perfused with culture media up to 72 h. For the first 24 h, the perfusion was kept at a flow rate that corresponded to a wall shear stress of 9.7 dynes/cm 2 which corresponds to average values seen in human capillaries (Figure 4(c)).…”
Section: Functional Characterization Of Iecsmentioning
confidence: 99%
“…Taken together, these results indicate a protective effect of the co-culture condition on the CMs as we have investigated in detail in our recent publication [33]. In order to evaluate the crosstalk between CMs and iECs in response to oxidative stress, the transcriptome of CMs in single culture or in the co-culture with iECs with or without H 2 O 2 treatment were profiled and screened for significantly changed genes.…”
Section: Resultsmentioning
confidence: 66%
“…Similarly, 3D cell culture technology has been used to study the effect of hypoxia in the context of ischemia in various cell types, including cardiomyocytes (152)(153)(154), astrocytes (155), endothelial cells (156), and hypoxia related to pulmonary fibrosis in fetal lung fibroblasts (157). Furthermore, the effects of both continuous hypoxia and IH on vascular sprouting has been explored in endothelial cells (158)(159)(160).…”
Section: D Cell Culturesmentioning
confidence: 99%